Tinjauan Hukum Pasal 28E Ayat (3) UUD 1945 dalam Pembatasan Kebebasan Berpendapat di Media Sosial di Indonesia - Dwi Saleha; Arief Fahmi Lubis; Dian Eriani; Sofian Sofian (Sanskara Hukum dan HAM, 2026)
This paper examines the normative legal implications of Article 28E Paragraph (3) of the 1945 Constitution of the Republic of Indonesia concerning restrictions on freedom of expression on social media. The Constitution guarantees the right to freedom of expression, but allows limitations under certain circumstances, particularly to maintain public order, national security, and morality. The emergence of social media platforms has complicated this balance, as they provide space for free expression while also posing risks such as the spread of misinformation, hate speech, and incitement to violence. This study analyzes the application of constitutional provisions, regulatory frameworks such as the Electronic Information and Transactions Law (ITE Law), and judicial interpretations of these laws. Through qualitative legal analysis, this paper discusses how Indonesian law regulates social media content and evaluates whether these legal limitations align with constitutional principles. The paper concludes that while social media regulation is necessary, existing laws need to be clearer and more specific to prevent abuse of authority and potential violations of freedom of expression.